Relationship between negative coping style and fear of COVID-19 among Wuhan college students during the post-pandemic period: A moderated chain mediation model - Yang, Lei; Yang, Ziyun; Xia, Ying (Frontiers in Psychiatry, 2022)
Objectives: After a long-term lockdown, particularly one in which human life is at risk, negative psychological consequences are expected. In this study, we aimed to explore the cause of stress and fear of coronavirus 19 (COVID-19) among Chinese college students in Wuhan during the latest strictest lockdown. Methods: During the COVID-19 outbreak, 1,070 college students from Wuhan, aged 18–29 years, took part in an online survey. We used correlations, bootstrap tests, and other statistical analysis methods to analyze the data. Results: Negative coping style significantly positively predicted fear of COVID-19, and stress had a significant mediating effect on the relationship between negative coping style and fear of COVID-19. In addition, rumination and stress had a chain-mediating effect on the relationship between negative coping style and fear of COVID-19. Perceived social support moderated the three paths of this serial mediation model. Conclusion: Negative emotions, such as stress and fear of COVID-19, in college students are caused by both behavior (e.g., negative coping style) and cognition (e.g., rumination). Importantly, negative cognitive thinking (i.e., rumination) is often a malign consequence of a negative coping style. Thus, to improve students’ mental health, students should be encouraged to engage in more positive behaviors and seek social support during periods of adherence to regular prevention and control measures.